Biodegradable spherical particles and production method therefor
Patent Information
- Application Number
- JP2024003370
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-06-17
AI Technical Summary
Existing biodegradable spherical particles used in cosmetics have issues with low sphericity, surface smoothness, and rapid biodegradation, leading to changes in tactile sensation during use.
Development of biodegradable spherical particles with a particle diameter variation coefficient of 40% or less, narrow particle size distribution, and controlled biodegradability, achieved through a melt-kneading method using biodegradable polymers like cellulose acetate and polyvinyl alcohol, ensuring slow decomposition and uniform particle shape.
The particles maintain a good tactile sensation over time by minimizing rapid decomposition, providing a stable texture and smoothness in cosmetic compositions.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to biodegradable spherical particles and a method for producing the same. In particular, the present disclosure relates to biodegradable spherical particles for use in cosmetic compositions and a method for producing the same. [Background technology]
[0002] Conventionally, cosmetics contain various polymeric microparticles for the purpose of improving spreadability, changing the texture, imparting a wrinkle-blurring effect, and improving the slipperiness of foundations and the like. Microparticles with particularly high sphericity have an excellent texture, and depending on their physical properties and shape, they can provide a light scattering (soft focus) effect. When such microparticles are used in foundations and the like, they can be expected to fill in and smooth out unevenness in the skin, and to scatter light in various directions, making wrinkles and the like less noticeable (soft focus).
[0003] The fine particles that have been used in such cosmetics are made of synthetic polymers such as polyamide, polymethyl methacrylate (PMMA), polystyrene, polypropylene, polyethylene, etc. However, in recent years, due to environmental considerations, there has been a demand for fine particles made of biodegradable materials that have the necessary properties and have a low environmental impact, instead of these synthetic polymers.
[0004] Patent Document 1 (Japanese Patent No. 6872068) discloses resin beads whose main component is cellulose, having a volume-based cumulative 50% particle size of 50 μm or less, a sphericity of 0.7 to 1.0, a surface smoothness of 70 to 100%, a solidity of 50 to 100%, a 5-day biodegradability of 20% or more measured in accordance with JIS K6950, and a cellulose content of 90 to 100% by mass in the resin.
[0005] Patent Document 2 discloses spherical cellulose powder having an average primary particle diameter of 5 μm or less, with the primary particle diameter of 90% or more by volume of the total particles being in the range of 2 to 7 μm, the ratio of the longest diameter to the shortest diameter of the sphere (longest diameter / shortest diameter) being in the range of 1.0 to 2.5, the haze value of a 20% by mass silicone oil paste being 70% or more, and the total transmittance being 95% or more.
[0006] Patent Document 3 describes a method of preparing a dispersion by kneading a resin component (A) such as a thermoplastic resin with a water-soluble auxiliary component (B), and then producing a molded body (e.g., a porous body or spherical particles) composed of the resin component (A) by eluting the auxiliary component (B) from the dispersion, and also describes that the resin component (A) can be a cellulose derivative, polylactic acid, or the like. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6872068 [Patent Document 2] JP 2013-221000 A [Patent Document 3] JP 2004-051942 A Summary of the Invention [Problem to be solved by the invention]
[0008] The particulate molded products obtained by the production method described in Patent Document 3 have low sphericity and are merely approximately spherical particles, and their biodegradability is also insufficient.
[0009] The microparticles mainly composed of cellulose disclosed in Patent Documents 1 and 2 have excellent biodegradability. However, the spherical particles described in Patent Document 2 have low surface smoothness, and therefore cannot provide a good tactile sensation. In addition, in cosmetics containing microparticles with excellent biodegradability, the microparticles may decompose after use, causing a change in the sensation when used. In particular, users are sensitive to changes in the sensation when used. There is a demand for biodegradable microparticles that cause little change in the sensation when used when incorporated into a cosmetic composition. The particles disclosed in Patent Document 1 cannot sufficiently suppress the change in the sensation when used.
[0010] An object of the present disclosure is to provide biodegradable spherical particles that can give cosmetic compositions that have a good feel to the touch and whose feel during use does not fluctuate over the short term, and a method for producing the same. [Means for solving the problem]
[0011] The biodegradable spherical particles according to the present disclosure contain a biodegradable polymer as a main component. The biodegradable spherical particles have a particle size coefficient of variation (CV) of 40% or less, and a biodegradability on the 5th day calculated by the following formula in a biodegradability test in accordance with OECD TG301F of 40% or less. Biodegradation degree (%)=(BOD-B) / TOD×100 (wherein BOD is the biochemical oxygen consumption (mg) of the test substance, B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) of the test substance.) Effect of the Invention
[0012] According to the present disclosure, the biodegradable spherical particles have a narrow particle size distribution and a substantially uniform particle size, thereby providing a good tactile sensation. The spherical particles have a low initial decomposition rate in a predetermined biodegradability test. In other words, the spherical particles decompose slowly and gently. In a cosmetic composition containing the spherical particles, the deterioration of the sensation of use caused by the rapid decomposition of the spherical particles is avoided. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a scanning electron microscope (SEM) image (magnification: 800 times) of the particles of Example A-1. [Diagram 2] FIG. 2 is a scanning electron microscope (SEM) image (magnification: 5000 times or more) of the particles of Example A-1. [Diagram 3] FIG. 3 is a scanning electron microscope (SEM) image (magnification: 800 times) of the particles of Comparative Example A-2. [Figure 4] FIG. 4 is a scanning electron microscope (SEM) image (magnification: 5000 times or more) of the particles of Comparative Example A-2. [Diagram 5] FIG. 5 is a scanning electron microscope (SEM) image (magnification: 800 times) of the particles of Example A-1 after the decomposition treatment. [Figure 6] FIG. 6 is a scanning electron microscope (SEM) image (magnification: 15,000 times) of the particles of Example A-1 after the decomposition treatment. [Figure 7] FIG. 7 is a scanning electron microscope (SEM) image (magnification: 800 times) of the particles of Comparative Example A-2 after the decomposition treatment. [Figure 8] FIG. 8 is a scanning electron microscope (SEM) image (magnification: 5000 times) of the particles of Comparative Example A-2 after the decomposition treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present disclosure will be described in detail below based on preferred embodiments. Each configuration and their combinations in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited by the embodiments, but only by the scope of the claims. In addition, each aspect disclosed in this specification can be combined with any other feature disclosed in this specification.
[0015] In this specification, the range "X to Y" means "X or more and Y or less", "ppm" means "ppm by weight", and unless otherwise noted, all test temperatures are room temperature (20°C ± 5°C).
[0016] [Biodegradable spherical particles] The biodegradable spherical particles of the present disclosure (hereinafter, sometimes referred to as "spherical particles") are particles mainly composed of a biodegradable polymer. Here, "main component" means that the component contained most abundantly among the constituent components of the particle is a biodegradable polymer, and the content thereof is at least 50% by weight. Furthermore, "biodegradable polymer" means a polymer that is decomposed in soil or seawater, or in a living body. In the present disclosure, a "polymer" is defined as a compound composed of one or more types of structural units repeatedly bonded together. As long as it exhibits a predetermined biodegradability, it may be a synthetic polymer or a polymer of natural origin.
[0017] Furthermore, the spherical particles have a particle size coefficient of variation CV of 40% or less, and in a biodegradability test in accordance with OECD TG301F, the degree of biodegradation on the 5th day calculated by the following formula is 40% or less. Biodegradation degree (%)=(BOD-B) / TOD×100 (wherein BOD is the biochemical oxygen consumption (mg) of the test substance, B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) of the test substance.)
[0018] The spherical particles of the present disclosure are made of a biodegradable material, and have an extremely good tactile feel due to their shape and narrow particle size distribution. By incorporating these spherical particles, a cosmetic composition of high quality with low environmental impact can be obtained. Moreover, the spherical particles of the present disclosure exhibit slower decomposition than particles made of conventional biodegradable materials. In cosmetic compositions containing these spherical particles, the feel of use, particularly the feel of touch, does not fluctuate in the short term. In this specification, the term "feel of touch" refers not only to the case where the spherical particles are directly touched, but also includes, for example, the feel of the skin and the feel of the particles when they are incorporated into a cosmetic composition.
[0019] The spherical particles of the present disclosure are biodegradable, and the decomposition rate is controlled. The biodegradability of the spherical particles can be evaluated by a biodegradability test in accordance with OECD TG301F. Specifically, the test substance (spherical particles) is dispersed in a medium (water), inoculated with an inoculum source (activated sludge from a sewage treatment plant), and cultured at 22°C ± 2°C for 28 days. The amount of oxygen consumed by the microorganisms to decompose the test substance (biochemical oxygen consumption) is measured over time, and the ratio to the theoretical oxygen consumption by the test substance is calculated as the biodegradability (%). The biodegradability in this specification is calculated at a test substance concentration of 100 mg / L, an inoculum source concentration of 30 mg / L, and a test liquid volume of 100 mL. This biodegradability (%) is calculated by the following formula. Biodegradation degree (%)=(BOD-B) / TOD×100 (wherein BOD is the biochemical oxygen consumption (mg) of the test substance, B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) of the test substance.)
[0020] According to OECD TG301F, a test substance with a biodegradability of more than 60% after 28 days is usually evaluated as "easily degradable". For example, microcrystalline cellulose exhibits a so-called sigmoid type decomposition behavior in which the decomposition reaction proceeds rapidly in the first 5 days after the start of the test, and then the decomposition rate decreases and reaches equilibrium. The present inventors considered that this rapid decomposition in the first 5 days after the start of the test is the cause of short-term fluctuations in the tactile sensation of a cosmetic composition containing spherical particles. They found that by lowering the initial decomposition rate of the biodegradable spherical particles and setting the biodegradability on the 5th day to 40% or less in the biodegradability test in accordance with the above-mentioned OECD TG301F, short-term changes in the feeling of use can be suppressed. That is, the spherical particles of the present disclosure differ from conventional biodegradable resin particles in that they have a small initial decomposition rate and show mild decomposition behavior. From the viewpoint of improving the stability of the feeling of use, the biodegradability of the spherical particles on the 5th day is preferably 35% or less, more preferably 30% or less. From the viewpoint of reducing the burden on the environment, the biodegradability on the fifth day is preferably 10% or more.
[0021] When the degree of biodegradation on day 5 measured by a biodegradability test in accordance with OECD TG301F is BD5 (%) and the degree of biodegradation on day 28 is BD28 (%), from the viewpoint of providing high biodegradability while suppressing fluctuations in the feeling of use, the ratio BD5 / BD28 of the spherical particles may be 0.60 or less, 0.55 or less, 0.50 or less, or 0.45 or less. From the viewpoint of improving biodegradability, the ratio BD5 / BD28 is preferably 0.10 or more.
[0022] From the viewpoint of suppressing fluctuations in the feeling of use while providing high biodegradability, it is preferable that the biodegradability on the 5th day BD5 and the biodegradability on the 28th day BD28 measured in a biodegradability test in accordance with OECD TG301F satisfy the following formulas. (BD28-BD5) / BD5 ≧ 0.50
[0023] In spherical particles having a ratio (BD28-BD5) / BD5 of the difference between BD28 and BD5 (BD28-BD5) to BD5 of 0.50 or more, the decomposition reaction is suppressed during the 5-day biodegradation test, and the decomposition reaction progresses during 5 to 28 days. From the viewpoint of improving biodegradability, this ratio (BD28-BD5) / BD5 may be 0.60 or more, 0.70 or more, or 0.80 or more. From the viewpoint of having little effect on the tactile feel at the beginning of use, the ratio (BD28-BD5) / BD5 is preferably 2.0 or less.
[0024] The spherical particles may have a biodegradability BD5 on the 5th day and a biodegradability BD28 on the 28th day, as measured by a biodegradability test in accordance with OECD TG301F, that satisfy the following formulas. (BD28-BD5) / BD28 ≧ 0.30
[0025] In spherical particles having a ratio (BD28-BD5) / BD28 of the difference between BD28 and BD5 (BD28-BD5) to BD28 of 0.30 or more, high biodegradability is achieved while suppressing the change in the tactile feel at the initial stage of use. From this viewpoint, the ratio (BD28-BD5) / BD28 may be 0.35 or more, 0.40 or more, or 0.45 or more, and may be 1.0 or less, or 0.90 or less.
[0026] The particle size variation coefficient CV of the spherical particles is 40% or less. The particle size variation of the spherical particles having a particle size variation coefficient CV of 40% or less is small. The spherical particles have a good touch. Furthermore, the particle size variation of the spherical particles is small, so that the decomposition reaction proceeds approximately uniformly in each particle. Therefore, even if the decomposition reaction proceeds and the particle size is reduced, a narrow particle size distribution is maintained. The touch of the spherical particles of the present disclosure does not deteriorate in the short term. From the viewpoint of stabilizing physical properties, the particle size variation coefficient CV of the spherical particles is preferably 38% or less, and preferably 35% or less. From the viewpoint of ease of production, the particle size variation coefficient CV of the spherical particles may be 0% or more, and may be 2% or more. The particle size variation coefficient CV is calculated by the following formula using the average particle size of the spherical particles and the standard deviation of the particle size, which will be described later. Coefficient of variation of particle size CV (%) = Standard deviation of particle size / Average particle size x 100
[0027] The average particle size of the spherical particles may be 0.08 μm or more, 0.1 μm or more, 1.0 μm or more, 2.0 μm or more, or 4.0 μm or more. Also, it may be 100 μm or less, 80 μm or less, 40 μm or less, 20 μm or less, or 10 μm or less. If the average particle size is too large, the touch is inferior and the light scattering (soft focus) effect is reduced. Also, if the average particle size is too small, production is difficult.
[0028] The average particle size and the particle size variation coefficient can be measured using a dynamic light scattering method. Specifically, the method is as follows. First, spherical particles are added to pure water to a concentration of 100 ppm, and a sample is prepared by suspending the particles in pure water using an ultrasonic vibration device. Then, the volume frequency particle size distribution is measured by a laser diffraction method (HORIBA, LTD. "Laser Diffraction / Scattering Particle Size Distribution Measuring Device LA-960", ultrasonic treatment for 15 minutes, refractive index (1.500, medium (water; 1.333)). In this volume frequency particle size distribution, the particle size corresponding to an integrated scattering intensity of 50% is determined as the average particle size. That is, the average particle size (μm) in this specification is the median size based on volume. The particle size variation coefficient is calculated from this median size and the standard deviation of the particle size.
[0029] The sphericity of the spherical particles of the present disclosure is preferably 0.7 to 1.0, more preferably 0.8 to 1.0, and even more preferably 0.9 to 1.0. If the sphericity is less than 0.7, the touch is poor, and for example, even when incorporated into a cosmetic composition, the touch and soft focus effect are reduced.
[0030] The sphericity can be measured by the following method. Using images of particles observed under a scanning electron microscope (SEM), the major axis and minor axis of 30 randomly selected particles are measured, the minor axis / major axis ratio of each particle is calculated, and the average of the minor axis / major axis ratios is taken as the sphericity. The closer the sphericity is to 1, the more the particle is considered to be a true sphere. Details of the measurement method will be described later in the examples.
[0031] The surface smoothness of the spherical particles of the present disclosure is 80% or more, preferably 85% or more, more preferably 90% or more, even more preferably 95% or more, and particularly preferably 98% or more, with the upper limit being 100%. If the surface smoothness is less than 80%, the desired tactile sensation may not be obtained, and the sensation of use may fluctuate in the short term. From the viewpoint of improving the tactile sensation and stabilizing the physical properties, the surface smoothness of the spherical particles may be 80 to 100%, 85 to 100%, 90 to 100%, 95 to 100%, or 98% to 100%.
[0032] The surface smoothness of the spherical particles can be determined by taking a scanning electron microscope photograph of the particles, observing the irregularities on the particle surface, and determining the surface smoothness based on the area of the concaves. Details of the method for measuring the surface smoothness will be described later in the Examples.
[0033] The shape of the spherical particles of the present disclosure is not particularly limited, and it is preferable that they have the above-mentioned sphericity and surface smoothness, but from the viewpoint of suppressing the initial decomposition rate and imparting a mild decomposition behavior that does not affect the touch, it is more preferable that the surface shape has few fine irregularities. The present inventors have focused on the fact that even particles with the same surface smoothness exhibit different decomposition behaviors depending on the difference in their surface shapes, and have found that the fine irregularities on the particle surface, which cannot be evaluated by the above-mentioned surface smoothness, affect the decomposition property of the particles, especially the initial decomposition property. For example, when a scanning electron microscope is used to observe a field of view of 0.5 mm x 0.5 mm at a magnification of 5000 times, if there are substantially no particles on whose surface there are micron-sized recesses, or when a field of view of 0.5 mm x 0.5 mm at a magnification of 5000 times is observed, if there are substantially no particles on whose surface there are micron-sized protrusions protruding from the virtual circle drawn along the arc of the spherical particles, the initial decomposition rate is suppressed, and a mild decomposition behavior is achieved. Here, the micron size refers to a range of 0.5 μm or more and less than 10 μm, and in the case of a roughly circular recess, this means that the diameter is about 0.5 to 10 μm.
[0034] Here, "substantially absent" is specifically defined as the average number of micron-sized recesses observed on the surface of a spherical particle being 3 or less, preferably 1 or less, when 30 randomly sampled particles are observed in a scanning electron microscope image at a magnification of 5000 times or more. It is also defined as the average number of micron-sized protrusions protruding from a virtual circle drawn along the arc of a spherical particle being 3 or less, preferably 1 or less, when 30 randomly sampled particles are observed in a scanning electron microscope image at a magnification of 5000 times or more.
[0035] The main component of the spherical particles in the present disclosure may be a biodegradable polymer selected from the group consisting of polysaccharides, polysaccharide esters, and aliphatic polyesters. The spherical particles may further contain a biodegradable polymer such as an aliphatic polyol, an aliphatic polycarbonate, or a polyacid anhydride, within the range in which the effects of the present disclosure can be obtained.
[0036] Polysaccharides refer to polymeric compounds in which monosaccharides are bound by glycosidic bonds. As long as the effects of the present disclosure can be obtained, the polysaccharides may be polymers of α-glucose or β-glucose. Examples of polysaccharides include cellulose, hemicellulose, pullulan, amylose, agarose, chitin, chitosan, carrageenan, pectin, dextrin, starch, collagen, mannan, arabinogalactan, glycogen, inulin, hyaluronic acid, and modified forms thereof. Two or more polysaccharides may be used in combination. One or two polysaccharides selected from cellulose and starch are preferred, and cellulose is more preferred. As long as the effects of the present disclosure can be obtained, the polysaccharides may be commercially available or may be polysaccharides obtained by hydrolyzing the polysaccharide esters described below. For example, in the case of cellulose, it may be a known fully saponified product of cellulose diacetate.
[0037] As long as the effects of the present disclosure are obtained, the weight-average molecular weight of cellulose is not particularly limited. The weight-average molecular weight of cellulose may be 10,000 or more, 20,000 or more, or 30,000 or more, and may be 500,000 or less, 400,000 or less, or 300,000 or less. The weight-average molecular weight of cellulose can be measured by size exclusion chromatography (GPC) measurement (GPC-light scattering method) in the same manner as the aliphatic polyester described later.
[0038] The polysaccharide ester is a carboxylate ester of the above-mentioned polysaccharide, and is defined as a compound in which a part of the hydroxyl groups in the molecular chain is replaced by an acyl group. An ester of one or two polysaccharides selected from cellulose and starch is preferred, and a cellulose ester is more preferred. Two or more polysaccharide esters may be used in combination. Other polysaccharide carboxylate esters not specified in this specification may be used as long as the effects of the present disclosure are obtained.
[0039] The total degree of substitution of the polysaccharide ester used in the spherical particles of the present disclosure is appropriately selected within the range of more than 0 and not more than 3.0 depending on the type of polysaccharide and the type of substituent. The total degree of substitution of the polysaccharide ester may be 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.5 or more, and may be 2.95 or less, 2.80 or less, 2.65 or less, 2.00 or less, 1.50 or less, 1.0 or less, or less than 0.7. The total degree of substitution of the polysaccharide ester is 13 C-NMR or 1 This can be measured by known methods using H-NMR.
[0040] From the viewpoints of availability and excellent biodegradability, the preferred polysaccharide ester is a cellulose ester, and a cellulose acylate having an acyl group having 2 or more carbon atoms is more preferred. The number of carbon atoms in the acyl group of the cellulose acylate may be 3 or more, 4 or more, 10 or less, or 8 or less. The cellulose acylate may have two or more types of acyl groups as substituents. In the present disclosure, two or more types of cellulose acylates having acyl groups with different carbon numbers may be used in combination as a biodegradable polymer.
[0041] Specific examples of cellulose acylate in the present disclosure include cellulose acetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose acetate butyrate, etc. From the viewpoints of biodegradability and easy availability, cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate are preferred, and cellulose acetate is more preferred.
[0042] The total degree of substitution of the cellulose acylate is appropriately selected within the range of more than 0 and not more than 3.0, as in the case of the polysaccharide ester described above, but from the viewpoint of obtaining good biodegradability, for example, the total degree of substitution of a cellulose acylate having an acyl group having 2 to 10 carbon atoms is preferably more than 0 and not more than 1.0. The total degree of substitution of this cellulose acylate may be 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.9 or less, 0.8 or less, or less than 0.7. Within the range in which the effects of the present disclosure can be obtained, cellulose acylates having different total degrees of substitution may be used in combination, and cellulose acylates having a total degree of substitution of more than 1.0 and not more than 3.0 may be mixed and used.
[0043] The degree of substitution of cellulose acylate can be measured by the following method. For example, it can be measured by NMR method according to the method of Tezuka (Tezuka, Carbonydr. Res. 273, 83 (1995)). That is, the free hydroxyl groups of cellulose acylate are acylated with a carboxylic anhydride in pyridine. The type of carboxylic anhydride used here should be selected according to the purpose of analysis. For example, acetic anhydride is suitable for analyzing the degree of propionyl substitution of cellulose propionate. The obtained sample is dissolved in deuterated chloroform, 13C-NMR spectrum is measured. When cellulose acylate having a propionyl group or cellulose acylate not having a propionyl group is treated with propionic anhydride to analyze the degree of propionyl substitution, the carbonyl carbon signal of the propionyl group appears in the same order from 2nd, 3rd, and 6th positions from the high magnetic field in the region from 172 ppm to 174 ppm. Since the total degree of substitution of cellulose acylate treated with carboxylic anhydride by Tezuka's method or a method similar thereto is 3.0, the sum of the areas of the carbonyl carbon signal of the acyl group originally possessed by the cellulose acylate and the carbonyl signal of the acyl group introduced by the carboxylic anhydride treatment is normalized to 3.0, and the abundance ratio of each acyl group at the corresponding positions (in other words, the area ratio of each signal) is obtained, which can be used as the degree of acyl substitution at the 2nd, 3rd, and 6th positions of the glucose ring in the cellulose ester. Needless to say, the only substituents containing acyl groups that can be analyzed by this method are those that do not correspond to the carboxylic anhydride used in the treatment for analysis. Also, 13 In addition to C-NMR, 1 It can also be analyzed by H-NMR.
[0044] As long as the effects of the present disclosure can be obtained, the weight average molecular weight of the cellulose acylate is not particularly limited. From the viewpoint of easily obtaining a desired shape, the weight average molecular weight of the cellulose acylate is preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 30,000 or more. From the viewpoint of high biodegradability and easily obtaining a desired spherical shape, the weight average molecular weight of the cellulose acylate is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 300,000 or less. The weight average molecular weight of the cellulose acylate can be measured by size exclusion chromatography (GPC) measurement (GPC-light scattering method) in the same manner as the aliphatic polyester described later.
[0045] The type of aliphatic polyester is not particularly limited, but examples thereof include, from the viewpoint of polymer structure, polyhydroxyalkanoic acid having, as a repeating unit, a structural unit obtained by polycondensation of hydroxyalkanoic acid, and a polymer having, as a repeating unit, a structural unit obtained by dehydration condensation of an aliphatic dicarboxylic acid and an aliphatic diol.
[0046] Examples of polyhydroxyalkanoic acids include polyglycolic acid, polylactic acid, poly(β-hydroxybutyric acid), poly(β-hydroxyvaleric acid), poly(lactic acid-co-glycolic acid), poly(β-hydroxybutyric acid-co-β-hydroxyvaleric acid), poly(β-propiolactone), poly(ε-caprolactone), etc. Examples of polymers with aliphatic dicarboxylic acids and aliphatic diols include polyethylene succinate, polybutylene succinate, poly(butylene succinate-co-butylene adipate), etc. Two or more of these may be used in combination.
[0047] From the viewpoints of availability and excellent biodegradability, the preferred aliphatic polyester is one or more selected from the group consisting of polycaprolactone, polyhydroxybutyric acid, and polylactic acid. Other aliphatic polyesters not specified in this specification may be used as long as the effects of the present disclosure are obtained.
[0048] From the viewpoint of facilitating the production of a desired particle shape, the weight average molecular weight of the aliphatic polyester is preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 50,000 or more.From the viewpoint of excellent biodegradability, the weight average molecular weight of the aliphatic polyester is preferably 5,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, and particularly preferably 250,000 or less.
[0049] The weight average molecular weight of the aliphatic polyester is determined by size exclusion chromatography (GPC) measurement using the following apparatus and conditions (GPC-light scattering method). Equipment: Shodex GPC "SYSTEM-21H" Solvent: Acetone Columns: 2 GMHxl (Tosoh), guard column (Tosoh TSKgel guardcolumn HXL-H) Flow rate: 0.8ml / min Temperature: 29℃ Sample concentration: 0.25% (wt / vol) Injection volume: 100μl Detection: MALLS (multi-angle light scattering detector) (Wyatt, "DAWN-EOS") MALLS correction standard material: PMMA (molecular weight 27600)
[0050] In another embodiment of the present disclosure, the spherical particles may contain a plasticizer. In the present disclosure, the plasticizer refers to a compound that can increase the plasticity of the biodegradable polymer described above. The type of plasticizer is not particularly limited, and examples thereof include dimethyl adipate, dibutyl adipate, diisostearyl adipate, diisodecyl adipate, diisononyl adipate, diisobutyl adipate, diisopropyl adipate, diethylhexyl adipate, dioctyl adipate, dioctyldodecyl adipate, dicapryl adipate, and dihexyldecyl adipate, di(ethylene glycol monoalkyl ether) adipate, di(diethylene glycol monoalkyl ether) adipate, and the like. adipic acid-based plasticizers including adipic acid esters such as di(triethylene glycol monomethyl ether) adipate, di(tetraethylene glycol monomethyl ether) adipate, di(pentaethylene glycol monomethyl ether) adipate, di(hexaethylene glycol monomethyl ether) adipate, di(propylene glycol monoalkyl ether) adipate, di(dipropylene glycol monomethyl ether) adipate, di(tripropylene glycol monomethyl ether) adipate, di(tetrapropylene glycol monomethyl ether) adipate, di(pentapropylene glycol monomethyl ether) adipate, di(hexapropylene glycol monomethyl ether) adipate, di(polyethylene glycol monoalkyl ether) adipate, di(polypropylene glycol monoalkyl ether) adipate, diphenyl adipate, dinaphthyl adipate, and dibenzyl adipate; citric acid plasticizers including citrate esters such as ethyl, acetyl tributyl citrate, isodecyl citrate, isopropyl citrate, triethyl citrate, triethylhexyl citrate, and tributyl citrate; glutaric acid plasticizers including glutaric acid esters such as diisobutyl glutarate, dioctyl glutarate, and dimethyl glutarate; succinic acid plasticizers including succinic acid esters such as diisobutyl succinate, diethyl succinate, diethylhexyl succinate, and dioctyl succinate;Examples of polybasic carboxylates include sebacic acid plasticizers including sebacic acid esters such as diisoamyl sebacate, diisooctyl sebacate, diisopropyl sebacate, diethyl sebacate, diethylhexyl sebacate, and dioctyl sebacate; and phthalic acid plasticizers including phthalic acid esters such as ethyl phthalate, methyl phthalate, diaryl phthalate, diethyl phthalate, diethylhexyl phthalate, dioctyl phthalate, dibutyl phthalate, and dimethyl phthalate. These polybasic carboxylates may be mixed-group polybasic acid esters.
[0051] Examples of the plasticizer contained in the spherical particles of the present disclosure include glycerin-based plasticizers including glycerin alkyl esters such as triacetin, diacetin, and monoacetin; neopentyl glycol; phosphoric acid-based plasticizers including phosphoric acid esters such as trioleyl phosphate, tristearyl phosphate, and tricetyl phosphate; di-2-methoxyethyl phthalate, dibutyl tartrate, o-benzoyl ethyl benzoate, ethyl phthalyl ethyl glycolate (EPEG), methyl phthalyl ethyl glycolate (MPEG), N-ethyl toluenesulfonamide, p-toluenesulfonic acid o-cresyl triethyl phosphate (TEP), triphenyl phosphate (TPP), and tributarybionin. The spherical particles may contain one or more plasticizers.
[0052] From the viewpoint of a high effect of plasticizing biodegradable polymers, polyvalent carboxylic acid plasticizers or glycerin plasticizers are preferred, and one or more selected from mixed-group polybasic acid esters and glycerin alkyl esters are more preferred. Examples of plasticizers for biodegradable polymers include those available under the trade name "DAIFATTY-10" manufactured by Daihachi Chemical Industry Co., Ltd., those available under the trade names "BIOCIZER", "Rikemal PL-004", and "Poem G-002" manufactured by Riken Vitamin Co., Ltd., and those available under the trade names "Polysizer" and "Monocizer" manufactured by DIC Corporation.
[0053] When the spherical particles of the present disclosure contain a plasticizer, the content of the plasticizer contained in the spherical particles is not particularly limited. For example, the content of the plasticizer in the spherical particles may be more than 0 parts by weight and not more than 120 parts by weight, may be 2 parts by weight or more and not more than 100 parts by weight, may be 10 parts by weight or more and not more than 80 parts by weight, or may be 15 parts by weight or more and not more than 50 parts by weight, relative to 100 parts by weight of the biodegradable polymer. The content of the plasticizer in the spherical particles is 1 It can be determined by H-NMR measurement.
[0054] In yet another embodiment of the present disclosure, the surface of the spherical particles may be partially or entirely covered with inorganic powder and / or an organic compound having a long-chain alkyl group. The inorganic powder and / or the organic compound having a long-chain alkyl group present on the particle surface allows the spherical particles to obtain surface properties suitable for the solvent and formulation used in the cosmetic composition. The spherical particles having inorganic powder and / or an organic compound having a long-chain alkyl group on their surface achieve high particle dispersibility in various solvents and formulations, and the tactile feel of the resulting cosmetic composition is improved. The inorganic powder and / or the organic compound having a long-chain alkyl group and the spherical particles may be in a physically attached state or a chemically bonded state.
[0055] As long as the effect of the present disclosure can be obtained, the particle shape of the inorganic powder is not particularly limited, and may be, for example, spherical, plate-like, needle-like, granular, or irregular. The average particle size of the inorganic powder is preferably smaller than the average particle size of the spherical particles, and may be, for example, 1 / 3 or less, or 1 / 10 or less, of the average particle size of the spherical particles. Here, the average particle size of the inorganic powder and the spherical particles means the median size based on volume.
[0056] The type of inorganic powder is not particularly limited, and examples thereof include titanium oxide, silicon oxide, aluminum oxide, zinc oxide, zirconium oxide, magnesium oxide, boron nitride, silicon nitride, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, mica, kaolin, sericite, mica, vermiculite, higilite, bentonite, montmorillonite, hectorite, kaolinite, zeolite, ceramic powder, hydroxyapatite, calcium phosphate, silicic acid, aluminum silicate, magnesium silicate, aluminum magnesium silicate, calcium silicate, etc. Two or more types may be used in combination. From the viewpoint of good adhesion to spherical particles and good tactile feel, one or more types selected from the group consisting of titanium oxide, silicon oxide, aluminum oxide, zinc oxide, and zirconium oxide are preferred.
[0057] The type of organic compound having a long-chain alkyl group is not particularly limited, but for example, the carbon number of the long-chain alkyl group may be 5 or more, 7 or more, 8 or more, or 22 or less. The carbon number of the long-chain alkyl group may be 5 or more and 22 or less, 7 or more and 22 or more, or 8 or more and 22 or less. Two or more organic compounds having different alkyl groups may be used in combination.
[0058] In the present disclosure, the organic compound having a long-chain alkyl group may be an amino acid derivative, and Nε-lauroyl-L-lysine is preferred as the amino acid derivative.
[0059] In the present disclosure, the organic compound having a long-chain alkyl group may be a cationic surfactant. Examples of the cationic surfactant include quaternary ammonium salts and / or amine salts. From the viewpoint of improving the touch and dispersibility, quaternary ammonium salts represented by the following general formula (1) are preferred. R 1 R 2 R 3 R 4 N + X - (1) (In the formula, X- is a halogen ion, and R 1 , R 2 , R 3 and R 4 are each independently an alkyl group having 1 to 25 carbon atoms which may have a substituent, and R 1 , R 2 , R 3 and R 4 At least one of the groups is an alkyl group having 12 or more carbon atoms. Specific examples of the cationic surfactant represented by formula (1) include stearyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, behenyl trimethyl ammonium chloride, distearyl diethyl ammonium chloride, decyl triethyl ammonium chloride, decyl dimethyl hydroxyethyl ammonium chloride, coconut oil trimethyl ammonium chloride, coconut oil methyl dihydroxyethyl ammonium chloride, myristyl trimethyl ammonium chloride, lauryl trimethyl ammonium chloride, distearyl dimethyl ammonium bromide, and stearyl trimethyl ammonium bromide.
[0060] The organic compound having a long-chain alkyl group may be a metal soap. A metal soap is defined as a non-alkali metal salt of a higher fatty acid. The higher fatty acid is preferably a fatty acid having 12 to 25 carbon atoms, and may be a saturated or unsaturated fatty acid. Examples of such fatty acid soaps include zinc salts, calcium salts, magnesium salts, or aluminum salts of lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, α-linolenic acid, erucic acid, and the like. An alkaline earth metal salt of a fatty acid having 12 to 25 carbon atoms is preferred, a zinc salt is more preferred, and zinc stearate is particularly preferred.
[0061] From the viewpoint of obtaining surface properties suitable for incorporation into a cosmetic composition, the amount of inorganic powder and / or organic compound having a long-chain alkyl group added is preferably 1.0% by weight or more, more preferably 3.0% by weight or more, and particularly preferably 5.0% by weight or more. From the viewpoint of not impairing the properties of the spherical particles, the amount of inorganic powder and / or organic compound having a long-chain alkyl group added is preferably 50.0% by weight or less, more preferably 30.0% by weight or less, and particularly preferably 10.0% by weight or less. When two or more inorganic powders and / or organic compounds having a long-chain alkyl group are used in combination, it is preferable that the total amount thereof satisfies the above-mentioned range.
[0062] [Cosmetic composition] The biodegradable spherical particles of the present disclosure can be suitably used in various cosmetic compositions. In a cosmetic composition containing these spherical particles, due to the shape of the spherical particles, the unevenness of the skin is filled and smoothed, and wrinkles and the like are made less noticeable by scattering light in various directions (soft focus). In addition, the spherical particles of the present disclosure have a narrow particle size distribution and a substantially uniform particle diameter, so that the cosmetic composition is given a good touch that has not been seen before. Furthermore, the spherical particles of the present disclosure have a slow initial decomposition rate compared to conventional spherical particles made of biodegradable polymers. Therefore, changes in the feeling of use due to the decomposition of the spherical particles are avoided. Even if the decomposition reaction of the spherical particles gradually progresses during use, the narrow particle size distribution of the spherical particles is maintained, so that the user is unlikely to feel a change in the touch. In this cosmetic composition, the feeling of use does not change in a short period of time, and a good touch is stably exhibited.
[0063] The cosmetic composition includes foundations such as liquid foundations and powder foundations; concealers; sunscreens; makeup bases; lipsticks and lipstick bases; face powders such as body powders, solid face powders, and face powders; solid powder eyeshadows; wrinkle concealing creams; and skin care lotions and other external preparations for skin and hair mainly intended for makeup, and the dosage form is not limited. The dosage form may be any of liquids such as aqueous solutions, emulsions, and suspensions; semi-solids such as gels and creams; powder solids such as powders and granules; and oil-based solids. In addition, the cosmetic composition may be an emulsion dosage form such as creams and emulsions; oil gel dosage forms such as lipsticks; powder dosage forms such as foundations; and aerosol dosage forms such as hair styling agents. The cosmetic composition containing the spherical particles of the present disclosure, particularly liquid foundations, is excellent in spreadability on the skin, pore covering power, and slipperiness.
[0064] [Method of producing biodegradable spherical particles] The spherical particles of the present disclosure can be obtained by carrying out the following steps in sequence. (1) Mixing a biodegradable polymer, a plasticizer, and a water-soluble polymer to obtain a mixture. (2) Melting and kneading the resulting mixture at a temperature of 200°C or higher and 280°C or lower to obtain a kneaded product. and (3) Removing the water-soluble polymer from the obtained kneaded product.
[0065] Conventionally, the emulsion method has been a common method for obtaining spherical particles using polymeric materials. For example, in the O / W emulsion method, a polymeric material is dissolved in an organic solvent to form an oil phase, and the oil phase is emulsified and dispersed in an aqueous phase to dissolve the organic solvent from the droplet-like oil phase to form polymeric particles. According to this O / W emulsion method, unevenness due to the dissolution path of the organic solvent is inevitably formed on the particle surface. In contrast, the spherical particles of the present disclosure are obtained by a melt kneading method that does not use an organic solvent, so that unevenness due to solvent dissolution is not formed on the particle surface, and spherical particles with extremely high surface smoothness are obtained. Here, the absence of unevenness on the particle surface means that when a field of view of 0.5 mm x 0.5 mm is observed at a magnification of 5000 times using a scanning electron microscope, there are substantially no particles on whose surface micron-sized recesses are observed, and when a field of view of 0.5 mm x 0.5 mm is observed at a magnification of 5000 times, there are substantially no particles on whose surface micron-sized protrusions are observed protruding from a virtual circle drawn along the arc of the spherical particle. In this disclosure, the definition of "substantially absent" is as described above.
[0066] The biodegradable polymer in the manufacturing method of the present disclosure is one or more selected from polysaccharides, polysaccharide esters, and aliphatic polyesters. The polysaccharides, polysaccharide esters, and aliphatic polyesters described above with respect to the spherical particles are appropriately selected and used. The polysaccharides, polysaccharide esters, and aliphatic polyesters can be manufactured by known methods. As long as the effects of the present disclosure can be obtained, commercially available biodegradable polymers may be used. The polysaccharides may also be obtained by hydrolyzing the polysaccharide esters by known methods. For example, when the biodegradable polymer is a polysaccharide ester, the kneaded mixture is treated with an alkali in the step of removing the water-soluble polymer from the kneaded mixture, whereby the polysaccharide esters are completely saponified, and spherical particles mainly composed of polysaccharides can be obtained. Details of the alkali treatment will be described later.
[0067] When cellulose acylate having a total degree of substitution of more than 0 and not more than 3.0 is used as the polysaccharide ester, the cellulose acylate is obtained through a process of activating raw pulp (cellulose), a process of acylating the activated cellulose with an esterifying agent (acylating agent), a process of deactivating the acylating agent after the completion of the acylation reaction, and a process of aging (saponification, hydrolysis) the produced cellulose acylate to adjust the total degree of substitution to a desired degree. In addition, before the activation process, a pretreatment process of disintegrating and crushing the raw pulp and then spraying and mixing with acetic acid may be included. After the aging (saponification, hydrolysis) process, a posttreatment process of precipitation separation, purification, stabilization, and drying may be included.
[0068] The total degree of substitution of cellulose acylate can be adjusted by adjusting the conditions of the aging process (conditions such as time and temperature). It is also possible to obtain a completely saponified cellulose by making the total degree of substitution substantially zero. The type of the substituent can be determined by selecting an esterification agent. Examples of the substituent include an acetyl group, a propionyl group, and a butyryl group. Two or more types of substituents can be introduced at a desired degree of substitution depending on the application.
[0069] The plasticizer used in the manufacturing method of the present disclosure may be any one that has a plasticizing effect in the melt extrusion of the biodegradable polymer, and the type is not particularly limited. It can be appropriately selected according to the type and physical properties of the biodegradable polymer used. Specifically, the above-mentioned plasticizers can be used alone or in combination of two or more types as the plasticizer contained in the spherical particles. From the viewpoint of high plasticizing effect of the biodegradable polymer, polyvalent carboxylic acid plasticizers or glycerin plasticizers are preferred, and one or more types selected from mixed-group polybasic acid esters or glycerin alkyl esters are more preferred.
[0070] The amount of the plasticizer may be more than 0 part by weight and not more than 120 parts by weight, may be 2 parts by weight or more and not more than 100 parts by weight, may be 10 parts by weight or more and not more than 80 parts by weight, or may be 15 parts by weight or more and not more than 50 parts by weight, relative to 100 parts by weight of the biodegradable polymer. If the amount is too small, the sphericity of the obtained spherical particles tends to decrease, and if the amount is too large, the particle shape cannot be maintained, and the desired spherical particles may not be obtained.
[0071] The type of water-soluble polymer used in the manufacturing method of the present disclosure is not particularly limited. Here, "water-soluble" means that when 1 g of the polymer is dissolved in 100 g of water at 25°C, the insoluble content is less than 50 wt%. In the present disclosure, the water-soluble polymer preferably has thermoplasticity. "Thermoplastic" means the property of softening and showing fluidity in a heated state and solidifying by cooling.
[0072] Examples of water-soluble polymers include polyvinyl alcohol, polyethylene glycol, sodium polyacrylate, polyvinylpyrrolidone, polypropylene oxide, polyglycerin, polyethylene oxide, polyvinyl acetate, modified starch, thermoplastic starch, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. Thermoplastic starch can be obtained by a known method. For example, referring to JP-B-6-6307 and WO92 / 04408, it can be produced by mixing tapioca starch with about 20% glycerin as a plasticizer and then kneading it with a twin-screw extruder.
[0073] In the production method of the present disclosure, the water-soluble polymer is preferably one or more selected from the group consisting of polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, and thermoplastic starch, more preferably one or more selected from the group consisting of polyvinyl alcohol and thermoplastic starch. The weight-average molecular weight of polyvinyl alcohol is preferably 500 or more and 50,000 or less.
[0074] The amount of the water-soluble polymer is preferably 110 parts by weight or more and 15,000 parts by weight or less, more preferably 180 parts by weight or more and 1,200 parts by weight or less, and even more preferably 200 parts by weight or more and 800 parts by weight or less, relative to 100 parts by weight of the biodegradable polymer. If the amount is less than 110 parts by weight, the surface smoothness may be low and irregularly shaped particles may be generated. If the amount exceeds 15,000 parts by weight, the particle size of the obtained spherical particles may be too small.
[0075] As long as the effects of the present disclosure are obtained, the mixing of the biodegradable polymer, the plasticizer, and the water-soluble polymer may be performed in one step or in multiple steps. The mixing of the biodegradable polymer, the plasticizer, and the water-soluble polymer may be performed by melt kneading. For example, the biodegradable polymer and the plasticizer may be mixed or melt kneaded to obtain a first mixture, and then the water-soluble polymer may be blended into this first mixture and mixed or melt kneaded.
[0076] Mixing of the biodegradable polymer and the plasticizer, or mixing of the biodegradable polymer, the plasticizer and the water-soluble polymer can be carried out in a dry or wet manner using a mixer such as a Henschel mixer. When using a mixer such as a Henschel mixer, the temperature inside the mixer is preferably a temperature at which the biodegradable polymer does not melt or decompose, for example, in the range of 20°C or higher and lower than 200°C.
[0077] Furthermore, when mixing the biodegradable polymer and the plasticizer, or mixing the biodegradable polymer, the plasticizer and the water-soluble polymer, by melt kneading, the materials may be mixed using a mixer such as a Henschel mixer at a temperature range of 20° C. or higher and lower than 200° C., and then melt kneading may be performed. By blending the biodegradable polymer and the plasticizer, or the biodegradable polymer, the plasticizer and the water-soluble polymer more uniformly and in a short time, the surface smoothness of the spherical particles that can be finally prepared is increased, improving the feel and tactile sensation.
[0078] The melt kneading may be performed by heating and mixing in an extruder. The kneading temperature (cylinder temperature) of the extruder may be in the range of 200°C to 230°C. Even at a temperature in this range, plasticization can be performed to obtain a uniform kneaded product. If the kneading temperature is too low, the sphericity and surface smoothness of the obtained particles may decrease, and the touch and optical properties may decrease. If the kneading temperature is too high, the kneaded product may be altered or discolored due to heat. In addition, the viscosity of the molten product may decrease due to a high kneading temperature, and therefore the kneading of the resin in the twin-screw extruder may be insufficient.
[0079] For example, when cellulose acylate is used as the biodegradable polymer, the kneading temperature (cylinder temperature) of the twin-screw extruder may be 200° C. The kneaded material may be extruded in a strand shape and then cut into pellets. In this case, the die temperature may be about 220° C.
[0080] In the manufacturing method of the present disclosure, a mixture containing a biodegradable polymer, a plasticizer, and a water-soluble polymer is melt-kneaded at 200° C. or more and 280° C. or less to obtain a kneaded product. When the biodegradable polymer, the plasticizer, and the water-soluble polymer are mixed by melt-kneading at 200° C. or more and 280° C. or less, the kneaded product obtained by mixing may be directly subjected to the next step.
[0081] An extruder such as a twin-screw extruder can be used to melt-knead the mixture. When an extruder is used, the kneading temperature means the cylinder temperature. The kneaded material containing the biodegradable polymer, etc. may be extruded in a string shape from a die attached to the tip of the extruder, and then cut into pellets. In this case, the die temperature may be 220°C or more and 300°C or less.
[0082] A dispersion is obtained in which the water-soluble polymer is used as a dispersion medium and the mixture of the biodegradable polymer and the plasticizer is used as a dispersoid by melt-kneading a mixture containing a biodegradable polymer, a plasticizer, and a water-soluble polymer at 200° C. or more and 280° C. or less. In other words, the kneaded product of the present disclosure is a dispersion in which approximately spherical particles containing a biodegradable polymer and a plasticizer are dispersed in a matrix made of a water-soluble polymer.
[0083] By removing the water-soluble polymer from this kneaded product, spherical particles are obtained which contain a biodegradable polymer as the main component, have a particle size coefficient of variation CV of 40% or less, and have a biodegradability of 40% or less on the 5th day in a biodegradability test in accordance with OECD TG301F.
[0084] As a method for removing the water-soluble polymer, the pressurized kneaded product is contacted with a good solvent for the water-soluble polymer, and the water-soluble polymer is removed by dissolving it in the solvent. Examples of the solvent include water; alcohols such as methanol, ethanol, and isopropanol; or mixed solvents thereof. Specifically, the pressurized kneaded product is mixed with a solvent to dissolve the water-soluble polymer in the solvent, and then the mixture is filtered to remove the residue, thereby removing the water-soluble polymer from the pressurized kneaded product.
[0085] In the process of removing the water-soluble polymer from the kneaded product after pressing, the plasticizer may or may not be removed together with the water-soluble polymer. Therefore, the obtained spherical particles may or may not contain a plasticizer.
[0086] From the viewpoint of high efficiency of removing the water-soluble polymer, the mixing ratio of the kneaded material to the solvent is preferably 0.01% by weight or more and 20% by weight or less, more preferably 2% by weight or more and 15% by weight or less, and even more preferably 4% by weight or more and 13% by weight or less, based on the total weight of the kneaded material and the solvent. If the kneaded material is more than 20% by weight, the water-soluble polymer may not be sufficiently removed. In addition, it may be difficult to separate the solid component containing the spherical particles from the liquid component in which the water-soluble polymer is dissolved by operations such as filtration and centrifugation.
[0087] From the viewpoint of high efficiency of removing the water-soluble polymer, the mixing temperature of the kneaded material and the solvent is preferably 0° C. or more and 200° C. or less, more preferably 20° C. or more and 110° C. or less, and even more preferably 40° C. or more and 80° C. or less. If the temperature is less than 0° C., the water-soluble polymer may not be sufficiently dissolved, making removal difficult. If the temperature exceeds 200° C., it may be difficult to obtain the desired particle shape due to deformation or aggregation of the particles.
[0088] The mixing time of the kneaded material and the solvent is not particularly limited and may be adjusted appropriately, and may be, for example, 0.5 hours or more, 1 hour or more, 3 hours or more, 5 hours or more, or 6 hours or less.
[0089] As a method of mixing the kneaded material with a solvent and dissolving the water-soluble polymer, for example, an ultrasonic homogenizer, a stirring device such as a three-one motor, etc. can be used. For example, when a three-one motor is used as the stirring device, the rotation speed during mixing of the kneaded material with the solvent may be 5 rpm or more and 3000 rpm or less. This allows the water-soluble polymer to be efficiently removed from the kneaded material. In addition, the plasticizer can be efficiently removed from the kneaded material.
[0090] When the biodegradable polymer is a polysaccharide ester, the kneaded mixture may be treated with an alkali in the step of removing the water-soluble polymer from the kneaded mixture, as described above. The alkali treatment saponifies the polysaccharide ester in the kneaded mixture to obtain a polysaccharide ester with a desired degree of substitution. Furthermore, by carrying out the alkali treatment under conditions for complete saponification, a polysaccharide with a degree of substitution of 0 can be obtained.
[0091] The alkali treatment is carried out by mixing the kneaded product with a solvent containing one or more metal compounds selected from alkali metal compounds and alkaline earth metal compounds in the step of removing the water-soluble polymer from the kneaded product. In other words, this manufacturing method further includes mixing the kneaded product with a solvent containing one or more metal compounds selected from alkali metal compounds and alkaline earth metal compounds to hydrolyze the polysaccharide ester when the biodegradable polymer is a polysaccharide ester. This solvent may be an aqueous solution of one or more metal compounds selected from alkali metal compounds and alkaline earth metal compounds. By washing the kneaded product with a solution containing this metal compound, the water-soluble polymer can be removed and the polysaccharide ester can be adjusted to a desired degree of substitution.
[0092] The alkali metal compounds and alkaline earth metal compounds include compounds of alkali metals such as sodium, lithium, potassium, etc., and alkaline earth metals such as calcium, magnesium, barium, etc. Hydroxides, oxides, or carbonates of alkali metals or alkaline earth metals are preferred, and hydroxides of alkali metals or alkaline earth metals are more preferred. Examples of such metal compounds include sodium hydroxide, magnesium hydroxide, calcium hydroxide, etc.
[0093] The amount of the metal compound to be added is appropriately selected depending on the type and degree of substitution of the polysaccharide ester, etc. When the water-soluble polymer is removed by repeating stirring and mixing of the kneaded product and the solvent and filtration multiple times, it is preferable to wash with a solution containing a metal compound at least once, and it is more preferable to wash with a solution containing a metal compound at the end of the removal step.
[0094] In another embodiment, the manufacturing method of the present disclosure may include adding and mixing inorganic powder to spherical particles obtained by removing the water-soluble polymer from the kneaded product. This results in spherical particles whose surfaces are partially or entirely covered with inorganic powder. The spherical particles further improve the tactile sensation.
[0095] From the viewpoint of obtaining a good touch, the inorganic powder is preferably one or more selected from the group consisting of titanium oxide, silicon oxide, aluminum oxide, zinc oxide and zirconium oxide. The amount of the inorganic powder added is preferably 0.01 part by weight or more and 1.0 part by weight or less per 100 parts by weight of the biodegradable polymer.
[0096] The method of adding inorganic powder to the spherical particles obtained by removing the water-soluble polymer and mixing them is not particularly limited, and a known mixing means is appropriately selected and used. Dry mixing or wet mixing may be used. For example, in the case of dry mixing, a mixing device such as a ball mill, a sand mill, a bead mill, a homogenizer, a planetary mixer, or a film mix may be used. The order of mixing the spherical particles and the inorganic powder is also not particularly limited. The spherical particles and the inorganic powder may be simultaneously charged into the mixing device, or a predetermined amount of inorganic powder may be charged into the mixing device and stirred (or pulverized while stirring), and then the spherical particles may be charged and mixed.
[0097] If necessary, the manufacturing method of the present disclosure may include a step of drying the obtained spherical particles after removing the water-soluble polymer and / or after adding and mixing the inorganic powder. The drying method is not particularly limited, and known methods such as heat drying, reduced pressure drying, and vacuum drying can be used. From the viewpoint of high drying efficiency, the drying temperature is preferably room temperature or higher, may be 50°C or higher, or may be 60°C or higher. From the viewpoint of suppressing thermal deterioration, the drying temperature is preferably 120°C or lower. EXAMPLES
[0098] The present disclosure will be specifically described below using examples, but the technical scope of the present disclosure is not limited to these examples. Each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the gist of the present disclosure.
[0099] (Example A-1) 100 parts by weight of cellulose acetate (manufactured by Daicel Corporation, total substitution degree = 2.4) as a biodegradable polymer and 25 parts by weight of triacetin (manufactured by Daicel Corporation) as a plasticizer were blended in a dry state, dried at 80 ° C for 12 hours or more, and further stirred and mixed using a Henschel mixer to obtain a mixture of biodegradable polymer and plasticizer. The obtained mixture was fed to a twin-screw extruder (PCM30 manufactured by Ikegai Corporation, cylinder temperature: 200 ° C, die temperature: 220 ° C), melt-kneaded and extruded to obtain pellets.
[0100] 30 parts by weight of the obtained pellets were blended in a dry state with 70 parts by weight of polyvinyl alcohol (manufactured by Nippon Synthetic Chemical Industry, melting point 190°C, saponification degree 99.1%) as a water-soluble polymer, and then fed into a twin-screw extruder (PCM30 manufactured by Ikegai Corporation, cylinder temperature 220°C, die temperature 220°C), melt-kneaded, and extruded to obtain a kneaded product containing a biodegradable polymer, a plasticizer, and a water-soluble polymer.
[0101] Separately, sodium hydroxide (manufactured by Nacalai Tesque, Inc.) was dissolved in pure water to prepare a 4.7 wt % aqueous sodium hydroxide solution as a solvent.
[0102] Next, the obtained kneaded material was mixed with the above-mentioned sodium hydroxide aqueous solution (solvent) so that the kneaded material was 5% by weight or less (= weight of kneaded material / (weight of kneaded material + weight of solvent) × 100), and stirred for 3 hours at a temperature of 80 ° C and a rotation speed of 100 rpm using a three-one motor (BL-3000 manufactured by Shinto Scientific Co., Ltd.). The stirred solution was filtered with filter paper (No. 5A manufactured by ADVANTEC), and the filtered material was taken out. The filtered material was mixed again with pure water to adjust the kneaded material to 5% by weight or less, and further stirred at a temperature of 80 ° C and a rotation speed of 100 rpm for 3 hours. After filtering, the operation of stirring the filtered material in water was repeated three or more times to obtain spherical particles of Example A-1.
[0103] The obtained spherical particles 1H-NMR analysis confirmed that the degree of acetyl substitution was 0.01, and that the main component of Example A-1 was substantially cellulose. In addition, a scanning electron microscope (trade name "TM3000" manufactured by Hitachi High-Technologies Corporation) was used to observe the sample of Example A-1. FIG. 1 is an example of an SEM image of Example A-1 taken at 800 times magnification. The length of the scale bar in FIG. 1 is 50.0 μm. In addition, a field of view of 0.5 mm × 0.5 mm was observed at 5000 times magnification, and it was confirmed that there were substantially no particles on whose surface micron-sized recesses were observed, and no particles on which micron-sized protrusions were observed protruding from a virtual circle drawn along the arc of the spherical particle were observed. The results are shown in Table 1 below as "SEM observation (magnification 5000 times)". Furthermore, the number of micron-sized recesses and the number of micron-sized protrusions were measured and averaged for 30 randomly sampled particles in SEM images at a magnification of 5000 times or more, and the average values were 0.50 and 0.47, respectively. Some SEM images of sampled spherical particles are shown in Figure 2. In each image in Figure 2, the areas surrounded by circles are micron-sized concaves, and the areas indicated by arrows are micron-sized convex parts protruding from an imaginary circle drawn along the arc of the roughly spherical particle.
[0104] The average particle size (μm), particle size variation coefficient (%), sphericity (%), and surface smoothness (%) of the spherical particles of Example A-1 were measured, and biodegradability and tactile sensation were evaluated. The tactile sensation was evaluated as tactile sensation 1 immediately after production and tactile sensation 2 after degradation treatment. The evaluation results are shown in Table 1. The average particle size, particle size variation coefficient, sphericity, surface smoothness, biodegradability, tactile sensation 1, and tactile sensation 2 were measured or evaluated by the following methods.
[0105] <Average particle size and particle size coefficient of variation CV> The particles were added to pure water to adjust the concentration to about 100 ppm, and a suspension was made using an ultrasonic vibration device. After that, the volume frequency particle size distribution was obtained and the average particle size was measured using the laser diffraction method (HORIBA, LTD. "Laser Diffraction / Scattering Particle Size Distribution Measuring Device LA-960" ultrasonic treatment for 15 minutes, refractive index (1.500, medium (water; 1.333)). The average particle size (μm) was taken as the particle size value (volume-based median size) corresponding to the cumulative 50% of the scattering intensity in the volume frequency particle size distribution. The particle size variation coefficient CV (%) was calculated by the standard deviation of the particle size / average particle size x 100. The results obtained are shown in Table 1 below.
[0106] <Sphericity> Using particle images observed under a scanning electron microscope (SEM), the long and short diameters of 30 randomly selected particles were measured, the short diameter / long diameter ratio of each particle was calculated, and the average of the short diameter / long diameter ratios was taken as the sphericity. The results are shown in Table 1 below.
[0107] <Surface smoothness> The images of the particles observed with a scanning electron microscope (SEM) were binarized using an image processing device, Winroof (Mitani Shoji Co., Ltd.) From the binarized images, a region including the center and / or the vicinity of the center of one particle was randomly selected, and the area ratio of the concave portion (shaded portion) of the concave portion in the selected region was calculated, and the surface smoothness (%) of one particle was calculated using the following formula. Surface smoothness of one particle (%) = (1 - concave area ratio) x 100 Concave area ratio=concave area in the given region / the given region The average surface smoothness of 10 randomly selected particle samples (n1 to n10) was taken as the surface smoothness (%). The larger this value, the higher the surface smoothness of the particle. The region used to calculate the area ratio may be any region smaller than the particle, including the center and / or the vicinity of the center of a single particle. The size of the region may be 5 μm square when the particle diameter is 15 μm.
[0108] <Biodegradable> In accordance with OECD TG301F, a biodegradability test was conducted on the particles under the following conditions. Inoculum source: return sludge from municipal wastewater treatment plants Target substance: Microcrystalline cellulose Test substance concentration: 100mg / L Target substance concentration: 100mg / L Inoculum concentration: 30mg / L Test liquid volume: 100mL Test temperature: 22℃±2℃ Culture period: 28 days
[0109] Thereafter, the biodegradability after 5 days BD5 (%) and after 28 days BD28 (%) were calculated using the following formula. The results are shown in Table 1 below. Biodegradation degree (%)=(BOD-B) / TOD×100 (wherein BOD is the biochemical oxygen consumption (mg) by the test material (particles), B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) by the test material.)
[0110] <Touch 1> A panel of 20 people conducted a sensory evaluation of the texture of the particles immediately after production. They touched the particles and evaluated the texture comprehensively based on smoothness and moistness using a maximum of 5 points according to the following criteria. The average score of the 20 people was calculated and is shown in Table 1 below as "Texture 1". Good: 5, Fair: 4, Average: 3, Fair: 2, Bad: 1
[0111] <Touch 2> Assuming that bacteria had somehow become contaminated into a cosmetic composition containing particles, cellulase was added as a simulation to carry out a decomposition process, and the change in the feel of the particles before and after decomposition was evaluated.
[0112] First, 3.0 g of particles were collected in a 100 mL screw tube, and 0.0030 g of cellulase (MP Biomedicals) and 30 mL of buffer solution (pH 5.0) were added. After immersion in a thermostatic chamber set at 40° C. for 24 hours, the supernatant was removed, and the particles were dried at 80° C. using a vacuum dryer to obtain particles after decomposition treatment. Figures 5 and 6 are examples of SEM images of Example A-1 after decomposition treatment at magnifications of 800 and 15,000, respectively. The length of the scale bar in Figure 5 is 50.0 μm, and the length of the scale bar in Figure 6 is 3.00 μm.
[0113] 5.0 g of each of the particles before the decomposition treatment and the particles after the 24-hour decomposition treatment were taken and added to 100 mL of water and stirred to prepare a suspension. Using this suspension, a panel test of 20 people was conducted to carry out a sensory evaluation before and after the decomposition treatment. Each suspension was used and evaluated comprehensively in terms of both smoothness and moist feeling, with a maximum score of 5 points, according to the following criteria. The average score of the 20 people was calculated and the result is shown in Table 1 below as "Touch 2 (before decomposition / after decomposition)". Good: 5, Fair: 4, Average: 3, Fair: 2, Bad: 1
[0114] (Examples A-2 to A-4) Spherical particles of Examples A-2 to A-4 were obtained in the same manner as in Example A-1, except that the concentrations of the aqueous sodium hydroxide solution were changed to 4.1 wt %, 3.7 wt %, and 3.2 wt %, respectively. 1 The total degree of substitution DS measured by H-NMR analysis, the physical properties of each particle evaluated by the above-mentioned method, and the results of SEM observation are shown in the following Table 1. In Table 1, "None" under "SEM observation (5000x)" means that when a field of view of 0.5 mm x 0.5 mm was observed at a magnification of 5000x, there were substantially no particles with micron-sized concaves or convexities on the surface.
[0115] (Examples A-5 and A-7) The spherical particles of Examples A-5 to A-7 were obtained in the same manner as in Example A-1, except that the biodegradable polymer was changed to that shown in Table 2 below, and distilled water was used instead of the sodium hydroxide solution. The average particle size (μm), particle size variation coefficient (%), sphericity (%), surface smoothness (%), biodegradability and touch 1 of each particle evaluated by the above-mentioned method, as well as the results of SEM observation, are shown in Table 2 below. In Table 2, "none" under "SEM observation (5000x)" means that there were substantially no particles with micron-sized concaves or convexities on the surface when a field of view of 0.5 mm x 0.5 mm was observed at a magnification of 5000x.
[0116] (Comparative example A-1) Commercially available microcrystalline cellulose (trade name "Ceolas-PH-101" manufactured by Asahi Kasei Corporation) was used as the particles of Comparative Example A-1. The particles of Comparative Example A-1 were used as the subject material and subjected to the biodegradability test described above. The average particle size (μm), particle size variation coefficient (%), sphericity (%), surface smoothness (%), biodegradability and touch 1 evaluated by the above-mentioned method, as well as the results of SEM observation, are shown in Table 2 below. In Table 2, "Not measurable" under "SEM observation (5000x)" means that the particle shape was irregular and therefore the surface shape could not be evaluated.
[0117] (Comparative example A-2) A cellulose acetate solution was prepared by dissolving 250 parts by weight of cellulose acetate (manufactured by Daicel Corporation, total acetyl substitution degree 2.4) in 2250 parts by weight of acetone (manufactured by Nacalai Tesque). A media phase was prepared by dissolving 200 parts by weight of polyvinyl alcohol (manufactured by Kuraray Co., Ltd.) in 2300 parts by weight of ion-exchanged water. The entire amount of the cellulose acetate solution was added to the obtained media phase and mixed, and the mixture was stirred at 3000 rpm for 3 minutes using a homodisper, and then further stirred at 2000 rpm for 10 minutes to obtain a suspension in which the cellulose acetate solution was uniformly dispersed in droplets. While stirring the suspension at 500 rpm using a homodisper, 112500 parts by weight of ion-exchanged water was poured in over 75 minutes to obtain a dispersion of cellulose acetate resin particles. The resin particles were filtered and washed, and then dispersed in 2500 parts by weight of ion-exchanged water. Sodium hydroxide was added to this dispersion to adjust the pH to 13.0 or less, and the dispersion was heated to 60° C. to carry out a hydrolysis reaction. After the hydrolysis reaction was completed, the dispersion was neutralized with hydrochloric acid, and the product was filtered and washed, and then peptized with ion-exchanged water. After further filtering and washing, the product was dried and crushed to obtain particles of Comparative Example A-2.
[0118] The obtained particles 1H-NMR analysis was performed to confirm that the main component of Comparative Example A-2 was substantially cellulose. In addition, the average particle size (μm), particle size variation coefficient (%), sphericity (%), surface smoothness (%), biodegradability, touch 1 and touch 2 evaluated by the above-mentioned method, and the results of SEM observation are shown in Table 2. Figure 3 is an example of an SEM image of Comparative Example A-2 taken at a magnification of 800 times. The length of the scale bar in Figure 3 is 50.0 μm. In Table 2, "Yes" in "SEM Observation (5000 times)" means that there were multiple particles with micron-sized recesses or protrusions on the surface when a field of view of 0.5 mm x 0.5 mm was observed at a magnification of 5000 times. Specifically, the number of micron-sized recesses and the number of micron-sized protrusions were measured and the average value was calculated for 30 randomly sampled particles in an SEM image of a magnification of 5000 times or more, and the results were 3.47 and 3.87, respectively. Some SEM images of sampled spherical particles are shown in Figure 4. In each image in Figure 4, the areas surrounded by circles are micron-sized concaves, and the areas indicated by arrows are micron-sized convex parts protruding from an imaginary circle drawn along the arc of the roughly spherical particle.
[0119] [Table 1]
[0120] [Table 2]
[0121] Details of the compounds shown in Tables 1-2 are as follows: CA: Saponified cellulose acetate (total degree of substitution 2.4, weight average molecular weight 47,000) manufactured by Daicel Corporation CA0: Completely saponified cellulose acetate (total degree of substitution 2.4, weight average molecular weight 47,000) manufactured by Daicel Corporation CAP: saponification product of cellulose acetate propionate (manufactured by Eastman Chemical: CAP-482-0.5, acetyl substitution degree = 0.18, propionyl substitution degree = 2.40) PCL: Polycaprolactone (weight average molecular weight 50,000) manufactured by Daicel Corporation PHB: Polyhydroxybutyric acid (weight average molecular weight 550,000) manufactured by Good Fellow
[0122] As shown in Table 1-2, it was confirmed that all of the spherical particles of the Examples had a good feel and exhibited slower biodegradability than the particles of the Comparative Examples. Also, as shown in Figure 1-8, in the Examples, the spherical particles were decomposed by cellulase from the surface, and maintained a roughly spherical shape even after the decomposition treatment, resulting in a decrease in feel 2 of only 0.3 points. In contrast, in the Comparative Examples, decomposition proceeded from the areas with significant irregularities, increasing the non-uniformity of the particle shape, resulting in a further decrease in feel 2 of 0.6 points.
[0123] (Example B-1) Preparation of Liquid Foundation The components shown in Table 3 were mixed, stirred thoroughly, and poured into a container to prepare a liquid foundation. The feel of the resulting liquid foundation was evaluated by the following method. The results are shown in Table 11.
[0124] [Table 3]
[0125] <Tactile sensation> A panel of 20 people conducted a sensory evaluation of the compositions immediately after they were prepared by blending the particles. Each composition was used and evaluated comprehensively in terms of both smoothness and moisturizing feeling according to the following criteria, with a maximum score of 5. The average score of the 20 people was calculated. Good: 5, Fair: 4, Average: 3, Fair: 2, Bad: 1
[0126] (Example B-2) Preparation of Sunscreen The components shown in Table 4 were mixed, stirred thoroughly, and poured into a container to prepare a sunscreen. The texture of the resulting sunscreen was evaluated using the method described above. The results are shown in Table 11.
[0127] [Table 4]
[0128] (Example B-3) Preparation of Powder Foundation The component A shown in Table 5 was roughly mixed in a Henschel mixer, and then the uniformly dissolved component B was added and mixed thoroughly, after which the mixture was poured into a container to prepare a powder foundation. The texture of the resulting powder foundation was evaluated using the method described above. The results are shown in Table 11.
[0129] [Table 5]
[0130] (Examples B-4 to B-6 and Comparative Examples B-1 to B-2) A liquid foundation was prepared in the same manner as in Example B-1, except that the spherical particles of Example A-1 in Table 3 were replaced with the particles of Examples A-4 to A-6 and Comparative Examples A-1 and A-2. The texture of each was evaluated by the method described above. The results are shown in Table 11.
[0131] (Example B-7) Preparation of makeup base Component C shown in Table 6 was dispersed in component A and thoroughly stirred. Then, component B was added, stirred, and filled into a container to prepare a makeup base. The texture of the obtained makeup base was evaluated by the method described above. The results are shown in Table 11.
[0132] [Table 6]
[0133] (Example B-8) Preparation of lipstick Component B shown in Table 7 was heated to 60°C and mixed thoroughly. Component C was added and thoroughly dispersed, and then component A was added and dissolved in a microwave oven, and then thoroughly mixed. The mixture was then heated and dissolved again in a microwave oven, poured into a mold, and cooled to solidify. This was placed in a lipstick container to prepare a lipstick. The feel of the resulting lipstick was evaluated using the method described above. The results are shown in Table 11.
[0134] [Table 7]
[0135] (Example B-9) Preparation of face powder The component A shown in Table 8 was thoroughly mixed using a mixer. The obtained powder was filled into a container to prepare a face powder. The texture of the obtained face powder was evaluated by the above-mentioned method. The results are shown in Table 11.
[0136] [Table 8]
[0137] (Example B-10) Preparation of white powder The talc and color pigment shown in Table 9 were mixed in a blender. The spherical particles of Example A-1 (CA0 spherical particles) and all the powder parts including the color pigment and talc previously mixed in the blender were mixed using a Henschel mixer. Then, oil (binder) was added and heated to 70°C, and further mixed, and then a pulverization process was performed as necessary. This was compression molded in a metal plate container to prepare a solid white powder. The texture of the obtained solid white powder was evaluated by the method described above. The results are shown in Table 11.
[0138] [Table 9]
[0139] (Example B-11) Preparation of solid powder eyeshadow After thoroughly mixing the powders shown in Table 10, the binder was dissolved uniformly and added to the powder portion and further mixed. Then, the mixture was compressed and molded to prepare a solid powder eye shadow. The texture of the obtained solid powder eye shadow was evaluated by the method described above. The results are shown in Table 11.
[0140] [Table 10]
[0141] [Table 11]
[0142] As shown in Table 11, the cosmetic compositions of Examples B-1 to B-11 containing the spherical particles of the present disclosure all had a good feel to the touch. From the results in Table 1-2, it is estimated that there is no sudden change in the feel to the touch even if the decomposition reaction of the spherical particles progresses.
[0143] [Disclosure items] Each of the following sections discloses a preferred embodiment.
[0144] [Item 1] Contains biodegradable polymers as the main component The particle size coefficient of variation (CV) is 40% or less. Biodegradable spherical particles that have a biodegradability of 40% or less on the fifth day, calculated using the following formula, in a biodegradability test in accordance with OECD TG301F. Biodegradation degree (%)=(BOD-B) / TOD×100 (wherein BOD is the biochemical oxygen consumption (mg) of the test substance, B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) of the test substance.)
[0145] [Item 2] 2. The biodegradable spherical particles according to item 1, wherein the ratio BD5 / BD28 of the biodegradability on day 5 (BD5) to the biodegradability on day 28 (BD28), as measured by a biodegradability test in accordance with OECD TG301F, is 0.60 or less.
[0146] [Item 3] 3. The biodegradable spherical particles according to item 1 or 2, wherein a biodegradability BD5 on the 5th day and a biodegradability BD28 on the 28th day, which are measured in a biodegradability test in accordance with OECD TG301F, satisfy the following formulas: (BD28-BD5) / BD5 ≧ 0.50
[0147] [Item 4] 4. The biodegradable spherical particles according to any one of items 1 to 3, wherein when observed under a scanning electron microscope at a magnification of 5000 times in a field of view of 0.5 mm x 0.5 mm, there are substantially no particles on whose surface micron-sized depressions are observed.
[0148] [Item 5] 5. The biodegradable spherical particle according to any one of items 1 to 4, wherein, when observed using a scanning electron microscope at a magnification of 5,000 times in a field of view of 0.5 mm x 0.5 mm, substantially no particles are found to have micron-sized protrusions protruding from an imaginary circle drawn along the arc of the spherical particle.
[0149] [Item 6] 6. The biodegradable spherical particle according to any one of items 1 to 5, wherein the biodegradable polymer is selected from the group consisting of polysaccharides, polysaccharide esters and aliphatic polyesters.
[0150] [Item 7] 7. The biodegradable spherical particles according to item 6, wherein the polysaccharide is one or two selected from cellulose and starch.
[0151] [Item 8] Item 8. The biodegradable spherical particles according to item 6 or 7, wherein the total degree of substitution of the polysaccharide ester is more than 0 and not more than 3.0.
[0152] [Item 9] 9. The biodegradable spherical particles according to any one of items 6 to 8, wherein the polysaccharide ester is a cellulose acylate having an acyl group having from 2 to 10 carbon atoms, and the total degree of substitution of the cellulose acylate is from more than 0 to 1.0.
[0153] [Item 10] 10. The biodegradable spherical particles according to any one of items 6 to 9, wherein the aliphatic polyester is a polyhydroxyalkanoic acid or a polymer of an aliphatic dicarboxylic acid and an aliphatic diol.
[0154] [Item 11] 11. The biodegradable spherical particles according to any one of items 6 to 10, wherein the aliphatic polyester is one or more selected from the group consisting of polycaprolactone, polyhydroxybutyric acid, and polylactic acid.
[0155] [Item 12] 12. A cosmetic composition comprising the biodegradable spherical particles according to any one of items 1 to 11.
[0156] [Item 13] mixing a biodegradable polymer, a plasticizer, and a water-soluble polymer to obtain a mixture; melt-kneading the mixture at 200°C or higher and 280°C or lower to obtain a kneaded product; and 2. The method for producing biodegradable spherical particles according to item 1, further comprising removing the water-soluble polymer from the kneaded mixture.
[0157] [Item 14] Item 14. The method for producing biodegradable spherical particles according to Item 13, further comprising, in the step of removing the water-soluble polymer from the kneaded mixture, mixing the kneaded mixture with a solvent containing one or more metal compounds selected from alkali metal compounds and alkaline earth metal compounds to hydrolyze the polysaccharide ester, when the biodegradable polymer is a polysaccharide ester.
[0158] [Item 15] Item 15. The method for producing biodegradable spherical particles according to item 14, wherein the solvent is an aqueous solution of the metal compound.
[0159] [Item 16] Item 16. The method for producing biodegradable spherical particles according to item 14 or 15, wherein the metal compound is a hydroxide of an alkali metal or an alkaline earth metal.
Claims
1. The product contains a biodegradable polymer as a main component, and in a biodegradability test in accordance with OECD TG301F, the biodegradability after 5 days calculated by the following formula is 40% or less, Biodegradable spherical particles, in which the ratio BD5 / BD28 of the biodegradability BD5 on the 5th day to the biodegradability BD28 on the 28th day as measured by a biodegradability test in accordance with OECD TG301F is 0.60 or less. Biodegradability (%) = (BOD-B) / TOD x 100 (Wherein, BOD is the biochemical oxygen consumption (mg) by the test substance, B is the biochemical oxygen consumption (mg) of the blank, and TOD is the theoretical oxygen consumption (mg) by the test substance.)
2. The biodegradable spherical particles described in claim 1, wherein the sphericity of the biodegradable spherical particles is 0.9 or more.
3. The biodegradable spherical particles described in claim 1, wherein the average particle diameter of the biodegradable spherical particles is 0.08 μm or more and 100 μm or less.
4. Biodegradable spherical particles as described in claim 1, wherein the standard deviation of the average particle diameter of the biodegradable spherical particles is 2.00 μm to 3.50 μm.
5. The biodegradable spherical particles according to claim 1, wherein the biodegradability BD5 on the 5th day and the biodegradability BD28 on the 28th day measured by a biodegradability test in accordance with OECD TG301F satisfy the following formulas: (BD28-BD5) / BD5 ≧ 0.50
6. 2. The biodegradable spherical particle according to claim 1, in which, when observed at a magnification of 5000 times using a scanning electron microscope over a field of view of 0.5 mm x 0.5 mm, substantially no particles have micron-sized depressions on their surface.
7. The biodegradable spherical particle according to claim 1, in which, when observed using a scanning electron microscope at a magnification of 5000 times over a field of view of 0.5 mm x 0.5 mm, substantially no particles are found to have micron-sized protrusions protruding from an imaginary circle drawn along the arc of the spherical particle.
8. 2. The biodegradable spherical particle according to claim 1, wherein the biodegradable polymer is selected from the group consisting of polysaccharides, polysaccharide esters and aliphatic polyesters.
9. The biodegradable spherical particle according to claim 8 , wherein the polysaccharide is one or two selected from cellulose and starch.
10. The biodegradable spherical particle according to claim 8 , wherein the polysaccharide ester has a total degree of substitution of more than 0 and not more than 3.
0.
11. 9. The biodegradable spherical particle according to claim 8, wherein the polysaccharide ester is a cellulose acylate having an acyl group having from 2 to 10 carbon atoms, and the total degree of substitution of the cellulose acylate is more than 0 and not more than 1.
0.
12. 9. The biodegradable spherical particle according to claim 8, wherein the aliphatic polyester is a polyhydroxyalkanoic acid or a polymer of an aliphatic dicarboxylic acid and an aliphatic diol.
13. The biodegradable spherical particle according to claim 8, wherein the aliphatic polyester is one or more selected from the group consisting of polycaprolactone, polyhydroxybutyric acid, and polylactic acid.
14. A cosmetic composition comprising the biodegradable spherical particles according to claim 1.
15. Mixing a biodegradable polymer, a plasticizer, and a water-soluble polymer to obtain a mixture; Melting and kneading the mixture at 200° C. or more and 280° C. or less to obtain a kneaded product; and The method for producing biodegradable spherical particles according to claim 1 , further comprising removing the water-soluble polymer from the kneaded mixture.
16. 16. The method for producing biodegradable spherical particles according to claim 15, wherein, in the step of removing the water-soluble polymer from the kneaded mixture, the kneaded mixture is mixed with a solvent containing one or more metal compounds selected from alkali metal compounds and alkaline earth metal compounds to hydrolyze the polysaccharide ester.
17. The method for producing biodegradable spherical particles according to claim 16, wherein the solvent is an aqueous solution of the metal compound.
18. The method for producing biodegradable spherical particles according to claim 16, wherein the metal compound is a hydroxide of an alkali metal or an alkaline earth metal.